2020
DOI: 10.3389/fpsyg.2020.568042
|View full text |Cite
|
Sign up to set email alerts
|

The Open Studio Approach to Art Therapy: A Systematic Scoping Review

Abstract: This research encompasses a systematic scoping review of literature and research pertaining to the open studio approach to art therapy, which originated with the work of artists in psychiatric hospitals in the 1940's. As art therapy became a profession, it sought recognition by adopting theories from other therapeutic disciplines. Today, however, there is an increase in the prevalence of studio practice that emphasizes art as the core of the therapeutic work; moreover, contemporary art therapy approaches even … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 49 publications
(75 reference statements)
0
16
0
Order By: Relevance
“…One of the main approaches in art therapy is the “art as therapy” approach, in which artwork is therapeutic in nature [ 27 ]. One model based on this approach is the open studio model [ 28 ].…”
Section: The Visual Art Medium As a Therapeutic Tool For Treating Chi...mentioning
confidence: 99%
See 2 more Smart Citations
“…One of the main approaches in art therapy is the “art as therapy” approach, in which artwork is therapeutic in nature [ 27 ]. One model based on this approach is the open studio model [ 28 ].…”
Section: The Visual Art Medium As a Therapeutic Tool For Treating Chi...mentioning
confidence: 99%
“…The open studio was developed to serve larger populations and communities in need, by making art-creative processes accessible [ 29 ]. A recently conducted systematic scoping review of the open studio model [ 28 ] revealed several core principles, including the central role of art, the experiential dimension of the creation of artwork, and the art therapist’s/facilitator’s role of holding a space to allow for a free creative process [ 28 , 30 ]. The open studio model seeks to offer a space that allows for the creative expression of the individual and the group [ 31 , 32 ]; it provides an egalitarian, nonhierarchical, open-minded, and community-like environment [ 30 , 33 ].…”
Section: The Open Studio Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, OS insists upon the individual’s focus on their own creative process within a group setting. This constitutes one of OS’ crucial priorities and strengths [ 14 ], and raises the question of whether it could be a first-tier intervention for identity development in teens suffering from MHC.…”
Section: Introductionmentioning
confidence: 99%
“…There is a long history of art therapy for treating psychosocial and mental health conditions. A manuscript by Finkel and Bat Or encompasses a systematic scoping review of literature and research pertaining to the art therapy open studio approach, which had origins with the work of artists in the 1940's in psychiatric hospitals [1]. This scoping review was not restricted to specific Corresponding Author: E-mail: deborah.hilton@gmail.com times, cultures, populations or settings.…”
Section: Introductionmentioning
confidence: 99%